Анализ возмущения решения задачи взвешенных наименьших квадратов - Химич, А.Н.; Николаевская, Е.А. (Теорія оптимальних рішень, 2007)
The weighed least squares problem is considered. Estimations of error of pseudosolution by perturbation of initial data of problem by condition of not saving of rank of the perturbation of matrix, etc rank(Ā) ≠ rank(A) are received.